Effect of total body fat on blood pressure in adolescents - Ansari, Aaqib Husain; Singh, Shraddha; Ghildiyal, Archna; Paisal, Aman; Mani, Chandra (International Journal of Research in Medical Sciences, 2024)
Background: Hypertension is a growing health concern among adolescents, with rising prevalence demanding a deeper understanding of its causes. Anthropometric factors are potential contributors to blood pressure variations, but their relationship with adolescent blood pressure remains unclear. Methods: A cross-sectional study of 110 adolescents at King George’s Medical College, Lucknow, from 20th June 2023 to 1st March 2024, examined the link between anthropometric parameters and blood pressure. Measurements followed standard protocols, and statistical analysis included correlation, linear regression, and multivariate methods. Results: Participants averaged 15.98 years, with mean height, weight, and BMI of 164.92 cm, 61.98 kg, and 22.48 kg/m². Diabetes history was reported in 23.64%, and 27.27% had hypertension. Average waist and hip circumferences were 84.49 cm and 93.43 cm, with body fat at 21.33%. Mean systolic and diastolic pressures were 120.36 mmHg and 77.15 mmHg, with 9.09% showing elevated blood pressure. Males had higher physical measurements and systolic pressure, while females had higher body fat. Systolic pressure correlated with age, size, and BMI, while diastolic pressure linked to weight, BMI, and body fat. Conclusions: Body measurements and fat levels significantly impact adolescent blood pressure. Higher body fat, waist circumference, and weight are linked to increased diastolic pressure, while systolic pressure correlates with age, height, and body size. Males tend to have higher systolic pressure and physical measurements, while females show higher body fat percentages. These findings highlight the importance of monitoring body composition to prevent hypertension and reduce cardiovascular risks in adolescents.